Governansi Digital: Transformasi Tata Kelola Pemerintahan di Era Digital (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Digital governance has become a new paradigm in the transformation of modern governance. This study examines the concept, implementation, and impact of digital governance on the effectiveness of public services. Through a qualitative descriptive analysis approach, this study identifies challenges and opportunities in the implementation of digital governance. The results of the study indicate that digital governance can increase transparency, accountability, and public participation, but requires an appropriate implementation strategy to overcome technological, regulatory, and human resource barriers.